2015
DOI: 10.1016/j.jash.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Morisky Medication Adherence Scale with therapeutic drug monitoring in apparent treatment–resistant hypertension

Abstract: The Morisky Medication Adherence Scale (MMAS-8) is a questionnaire developed for screening of non-adherence in patients with several chronic conditions, including uncomplicated hypertension. However, its accuracy in predicting nonadherence in patients with apparent treatment-resistant hypertension (a-TRH) is not known. Accordingly, we performed a retrospective study in 47 patients with a-TRH who had completed the eight-item MMAS during the initial clinic visit. Non-adherence was defined as presence of undetect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 24 publications
(27 reference statements)
6
53
0
4
Order By: Relevance
“…Finally, 28 articles were included in the systematic review and 25 of these were included in the meta-analysis. [9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][27][28][29][30][31][33][34][35][36] …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, 28 articles were included in the systematic review and 25 of these were included in the meta-analysis. [9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][27][28][29][30][31][33][34][35][36] …”
Section: Resultsmentioning
confidence: 99%
“…Nine of the studies were conducted in the United States, [11,12,15,26,29,30,32,33,35] and 2 each in China, [11,17] Nigeria, [16,22] Hong Kong, [21,25] and Iran. [10,18] Countries such as Uganda, Lebanon, Kenya, Republic of Korea, Peru, Ethiopia, Ghana, Malaysia, Palestine, Brazil, and Italy were represented with a single study.…”
Section: Characteristics Of Studies Assessedmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the protocol, the assessment of treatment compliance was assessed by the structured anamnesis based on the Morisky medication adherence scale, which was suggested to have limited accuracy in detecting medication nonadherence in patients with resistant hypertension by Pandey et al The results of this small study were published after all patients in the presented study were recruited, at which point no changes to the protocol were allowed. 33 It should be noted, however, that several studies have recently shown that nonadherence to treatment is not affected by RDN, nor did it influence RDN results. [34][35][36][37] Moreover, this limitation is compensated for by strict inclusion criteria and by the fact that all patients maintained their baseline antihypertensive drug regimen for the 3-month follow-up.…”
Section: 18mentioning
confidence: 94%